The Importance of Carbohydrate Intake for Maintaining Glycogen Stores and Physical Performance during Prolonged Exercise : A Literature Review - Ismardi Ismardi; Dally Rahman; Muhamad Sazeli Rifki; Wilda Welis; Ardo Okilanda; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
The study investigates the critical role of carbohydrate intake in maintaining glycogen stores and enhancing physical performance during prolonged exercise. The primary aim is to evaluate how carbohydrate consumption influences glycogen levels and athletic performance, focusing on intake types and timing. Utilizing a qualitative descriptive research model, the study conducts an extensive literature review, involving a thorough search of scientific databases such as Scopus, ScienceDirect, and Google Scholar. Specific keywords like